An assessment of the impact of 'free-carry', on mining policy, regulations and the institutional framework for acquisition : a case study of South Africa - Gerber, Leonardus J. (University of Pretoria, 2023)
Dissertation (LLM (Extractive Industries Law in Africa))--University of Pretoria, 2018.